Primary mesenteric liposarcoma with multiple mesenteric lipomas and Meckel’s diverticulum (Indian Journal of Case Reports, 2020)
Abdominal liposarcomas more commonly arise from the retroperitoneum. However, primary mesenteric liposarcoma is a rare neoplasm. Primary mesenteric liposarcoma is a rare diagnosis; hence, a differential diagnosis of an abdominal mesenteric tumor should also be considered. Here, in this case, report, we are reporting a well-differentiated primary mesenteric liposarcoma with Meckel’s diverticulum, which has not been reported till now. The clinical findings and imaging were more suggestive of the gastrointestinal stromal tumors, but on laparotomy, it turned out to be primary mesenteric liposarcoma (well-differentiated) with multiple mesenteric lipomas and Meckel’s diverticulum.